Political Philosophy and Rational injustice: From normative to Critical Theory - McCarthy, Thomas (Estudios de Filosofía, 2005)
Although “race”, i.e. racial representations and classifications, has been a major structural feature of political life throughout the modern period, the normative political theory that dominates Anglo-American political philosophy has not systematically incorporated it as such — in the way that it did “class” in the late nineteenth century and has recently attempted to do with “gender” and “culture.” A close analysis of John Rawls’s influential distinction between “ideal” and “non-ideal” theory points to a diagnosis of the problem and suggests a cure: a form of critical theory that combines the constructive and reconstructive aims of normative theory with the interpretive and explanatory aims of empirically based studies and with the practical aims of social and political critique.